Silent Killers: The Alarming Impact of Microplastics Polystyrene on Catfish Liver Health - Suhardi, Haidar Rafli Putra; Moch Irfan Hadi; Atiqoh Zummah (Universitas Airlangga, 2025)
Introduction: The presence of microplastics in the bodies of living things has become a matter of concern. One example is the widespread use of polystyrene microplastics, which have been widely used by industry even medical products. Styrene bonds and Benzyl Carbon in polystyrene have been identified as potential sources of free radical formation. Upon decomposition, these bonds release dissolved organic carbon, which has been identified as a significant contributor to chemical pollution. Methods: This study aims to determine the effect of microplastic polystyrene in experimental research (MP-PS measuring +0.5 mm) on catfish Clarias gariepinus with concentrations of 1, 1.5, 2, 2.5, 3 mg (K1-K5) for one month on fish liver histopathology. Histopathological observation of fish liver using parrafin method and statistical analysis using SPSS was tested using Anova. Results and Discussion: As determined by the analysis of variance (ANOVA) statistical test (P>0.05), it showed that MP-PS had a significant effect on liver damage in catfish, resulting in the most severe liver damage and the least damage depending on the amount of MP-PS given to the fish. Additional data were obtained in the form of liver tissue abnormalities. Conclusion: The toxicological effects of polystyrene microplastics (MP-PS) on catfish liver health, demonstrating a dose-dependent relationship. Higher MP-PS concentrations led to severe histopathological damage, including several types of liver cell abnormalities. These findings emphasize the urgent need for stricter regulations on microplastic pollution, as its unregulated production threatens aquatic ecosystems and public health.